INCREASING STUDENTS’ SPEAKING ABILITY AND ACTIVE PARTICIPATION IN THE CLASSROOM THROUGH THINK-PAIR-SQUARE STRATEGY - Zainollah Zainollah (Kariman: Jurnal Pendidikan dan Keislaman, 2014)
This study is categorized as classroom action research (CAR). This study proposed Think-Pair-Square as strategy in English language teaching and learning of speaking at the second grade of MTs Mambaul Ulum Bata-Bata Palengaan Pamekasan. This strategy is aimed at solving the students’ problems on speaking ability and active participation in the classroom. Based on the preliminary study, the students’ problems in speaking skill grouped into several problems: (1) lack of vocabularies (2) lack of ideas to speak (3) afraid to speak (4) lack of self-confidence. Therefore, the criteria of success were directed to the mentioned problems. The result of the research showed that by implementing Think-Pair-Square strategy in English language teaching and learning of speaking skill in the classroom, the students speaking ability is increased and students’ active participation during the speaking activities in the classroom is very highly positive and increased.